Development and Validation of UPLC-MS/MS Method for Determination of Enasidenib in Rat Plasma and Its Pharmacokinetic Application - Shuang-long Li; Yong-liang Zhu; Yi Zhang; Shu-han Liu; Xiang-die Wang; Xiang-jun Qiu (International Journal of Analytical Chemistry)
In our research, a straightforward UPLC-MS/MS method, with diazepam as the internal standard (IS), was proposed and acknowledged to determine the concentrations of enasidenib in rat plasma. When preparing the sample, we used acetonitrile for protein precipitation. The gradient elution method was used, and the mobile phase was acetonitrile and 0.1% formic acid. Diazepam was used as the IS. We used the Acquity UPLC BEH C18 column to separate enasidenib and IS. Under the positive ion electrospray ionization (ESI) source conditions, the mass transfer pairs of enasidenib were monitored by multiple reaction monitoring (MRM) to be m/z 474.2 ⟶ 456.1 and m/z 474.2 ⟶ 267.0, and the IS mass transfer pairs were m/z 285.0 ⟶ 154.0. Enasidenib had good linearity (r2 = 0.9985) in the concentration range of 1.0–1000 ng/mL. Besides, the values of intraday and interday precision were 2.25–8.40% and 3.94–5.46%, respectively, and the range of the accuracy values varied from −1.44 to 2.34%. Matrix effect, extraction recovery, and stability were compliant with FDA approval guidelines in terms of bioanalytical method validation. We had established a new method that had been applied to the pharmacokinetic study of enasidenib in rats.